ADDITION OF Aurantiochytrium sp. MEAL IN THE DIET AFFECTS IMMUNITY AND THERMAL SHOCK RESISTANCE OF THE PACIFIC WHITE SHRIMP - Jamilly Sousa ROCHA; Mariana SOARES; Ariane Martins GUIMARÃES; Delano Dias SCHLEDER; Walter Quadros SEIFFERT; Felipe do Nascimento VIEIRA (Boletim do Instituto de Pesca)
This paper reports the evaluation of digestibility, immunological parameters, and resistance to thermal shock at low temperature in Litopenaeus vannamei fed diets with diferent Aurantiochytrium sp. meal additions (0; 0.5; 1 and 2%). First, the apparent digestibility coefficient of the ingredient was determined. The digestibility of the microalgae meal was high for protein (74.90%); around 60% for lipids, and for docosahexaenoic fatty acid (DHA) it was 55.61%. After, shrimp rearing with the feed additive was carried out in a clear water system, containing 25 shrimp (initial weight: 4.89 Â± 0.27 g) per 400 L tank. Feeding occurred four times a day. After a three-week period, immunological parameters were evaluated and thermal shock was performed. Animals fed 0.5% and 2% of the microalgae Aurantiochytrium sp. showed higher survival to thermal shock. In immunological analyses, the serum agglutiniting titer was higher (p <0.05) in the 0.5 and 2% additions of the microalgae meal, and the phenoloxidase activity (PO) was higher in the 1% addition (p <0.05). It is concluded that there is good utilization of the nutrients of Aurantiochytrium sp. meal by L. vannamei and its addition to the diet (0.5 and 1%) increased shrimp resistance to thermal shock.